Expanding Argument Instruction: Incorporating Multimodality and Digital Tools. Issue 5 (7th November 2017) - Howell, Emily
Abstract: The researcher conducted a formative experiment in a ninth‐ and a 10th‐grade English classroom to observe a multiliteracies‐based intervention implemented to improve high school students' arguments. Traditionally, argument is taught from a cognitive perspective, emphasizing concepts such as claims, evidence, and warrants. However, arguments are also creations of social practice that incorporate the multimodality that digital tools afford. The author discusses three assertions regarding multimodality, social practice and digital tools, and transfer in relation to expanding argument instruction.